2020
DOI: 10.1021/acsomega.9b04079
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting Antibacterial Activity of a Synthesized Mn2+ Complex of Curcumin on Gram-Positive and Gram-Negative Bacterial Strains

Abstract: Curcumin is an important molecule with a plethora of pharmacological activities and therapeutic potentials. Despite its efficacy, it remained a potential drug candidate owing to hydrolytic instability and poor aqueous solubility. To overcome the limitations related to low solubility, low bioavailability, and the fact that curcumin is never present in solution as a “single unit”, its complex was prepared with Mn II with the idea that binding to a metal ion might help to resolve these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…Since biological targets were present in the immediate vicinity of in situ electrochemically generated quinone-dianion or semiquinone they get an opportunity to interact with reduced species. In aerated medium, there is a possibility for the formation of superoxide radical anion and that here the Mn II complex could show SOD activity [ 53 ]. The time for in situ electrochemical generation of species was kept a constant so that similar charge was made available to each compound in all the sets of the experiment and that there is similar experimental error associated with the stimuli (here, the potentiostat) that helps to generate the reactive species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since biological targets were present in the immediate vicinity of in situ electrochemically generated quinone-dianion or semiquinone they get an opportunity to interact with reduced species. In aerated medium, there is a possibility for the formation of superoxide radical anion and that here the Mn II complex could show SOD activity [ 53 ]. The time for in situ electrochemical generation of species was kept a constant so that similar charge was made available to each compound in all the sets of the experiment and that there is similar experimental error associated with the stimuli (here, the potentiostat) that helps to generate the reactive species.…”
Section: Methodsmentioning
confidence: 99%
“…Since Mn II complexes show significant SOD like activity and because Mn II is able to acquire higher oxidation states in presence of peroxides that are generated as part of ROS, we wanted to see if the Mn II complex would be beneficial for cell killing [ 52 , 53 ]. It is reported that almost all mitochondria contain a form of Mn-SOD where Mn could be in +2 or +3 oxidation states [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc-curcumin Increases antioxidant enzymes and decreases MDA level caused by cold-restraint stress in mice [17] Iron-curcumin Improves antioxidant activity [18] Gold NP-curcumin Shows good antioxidant activity [19] Silver-curcumin Presents good antioxidant activity and cell compatibility [20] Copper-curcumin Zinc-curcumin Enhances the superoxide dismutase, catalase, and glutathione peroxidase activities and attenuates MDA levels in PC12 cells [21] Copper-curcumin Exhibits antioxidant potential by scavenging DPPH radicals [11] Zinc NP-curcumin Exerts antioxidant activity as it scavenges ABTS+ and DPPH free radicals [22] Ruthenium-curcumin Exhibits potent antioxidant activity [23] Gallium-diacetylcurcumin Presents an increase in the antioxidant efficiency [24] Anti-inflammatory Zinc-curcumin Suppresses NF-κB, TGF-β1, IL-8, IL-6, TNF-α in rat model [25,26] Copper-curcumin Suppresses PKCδ and NF-κB [27] Zinc-curcumin Copper-curcumin Inhibits H 2 O 2 -induced NF-κB in PC12 cells [21] Gadolinium-curcumin Inhibits pIKKα, pIKKα/β, and NF-κB in pancreatic cancer cells [28] Anti-microbial Cobalt-, Nickel-, Copper-curcumin Inhibits growth of E. coli, S. aureus, K. pneumoniae, S. pyogenes, and P. aeruginosa [29] Zinc-curcumin Inhibits growth of P. aeruginosa [30] Zinc-curcumin Inhibits growth of B. subtilis, E. coli [22] Ruthenium-curcumin Inhibits growth of drug resistant S. aureus, reduces mean bacterial counts in murine model of Staphylococcus infection [31,32] Manganese-curcumin Inhibits growth of S. aureus, E. coli [32] Silver-curcumin Combats multiple bacteria-induced infections on wound surfaces [20] Copper-curcumin Exhibits antimicrobicidal activity [33] Copper-curcumin Inhibits growth of P. aeruginosa [34] Orthovanadium-curcumin Inhibits bacterial biofilm formation, growth of S. aureus and E. coli [35] Copper-curcumin Inhibits growth of P. aeruginosa and biofilm formation [34] Ruthenium-curcumin Exhibits strong antibiofilm activity [31] Zinc-curcumin Exerts potency against biofilm formation [30]…”
Section: Antioxidantmentioning
confidence: 99%
“…The Mn 2+ -curcumin complex has been shown to possess significant antibacterial activity against both Gram-negative (E. coli) and Gram-positive (S. aureus) bacteria compared to free curcumin [32]. Another curcumin complex with rare earth metal (rare earth(III) nitrate) also exhibited strong antibacterial activity compared to that of curcumin alone [50].…”
Section: Antimicrobialmentioning
confidence: 99%
See 1 more Smart Citation